The Effect of the Self-Regulated Learning Model on Students' Mathematical Literacy: Case on Linear Equation System - Mohamad, Faisal; Pomalato, Sarson W.; Takaendengan, Bertu Rianto (IKIP Siliwangi, 2026)
This study aims to examine the influence of Self-Regulated Learning (SRL) on students’ mathematical literacy skills in the topic of Three-Variable Linear Equation Systems (SPLTV). Mathematical literacy is understood as the ability to formulate, employ, and interpret mathematical concepts in solving contextual problems. The background of this research arises from the low mathematical literacy skills of students at SMK TRIDARMA, as observed through initial observations and the 2024 education report. Many students struggled to identify essential information, apply mathematical procedures correctly, and interpret their solution results logically. Self-regulated learning was implemented to help students take greater responsibility for their learning process through the phases of planning, monitoring, evaluation, and reflection. This study employed a quasi-experimental method with a Pretest–Posttest Control Group Design. The research sample consisted of two eleventh-grade classes: the experimental class, which was taught using the self-regulated learning model, and the control class, which received direct instruction. Data on students’ mathematical literacy skills were collected through essay tests that had been validated by experts. The data were analyzed using ANCOVA to determine the effect of the treatment after controlling for students’ initial abilities. The results showed a significant difference between the two groups. The obtained F count of 97.02083 exceeded the F table value of 4.105, indicating that self-regulated learning had a positive and significant effect on students’ mathematical literacy skills. Students in the experimental class demonstrated greater improvement compared to those in the control class. Thus, it can be concluded that Self-Regulated Learning is effective in enhancing students’ mathematical literacy skills on SPLTV material.